CORPORATE SOCIAL RESPONSIBILITY DALAM PEMIKIRAN BUDAYA JAWA BERDIMENSI “HAMEMAYU HAYUNING BAWANA” (Pendekatan Studi Hermeneutika) - Resha Dwiayu Pangesti (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2017)
Corporate Social Responsibility (CSR) is a phenomenon and strategy that companies use to accommodate the needs from stakeholder interests. This program is a form of corporate responsibility to reduce social disturbance and is believed to improve the relationship between humans, nature and God. The purpose of this article is to reveal the meaning that social and environmental accounting can be viewed in the perspective of Hamemayu Hayuning Bawana, a corporate social responsibility (CSR) program as a form of corporate responsibility report on the environment, education and social activities to achieve perfection of life of the company. The hermeneutical study approach is a method of this research used to reveal the meaning of the text of Javanese philosophy Hamemyu Hayuning Bawana. The concept of Cororate Social Responsibility is part of a form of alignment of life for social activities in achieving perfection of life in accordance with the philosophy of Hamemayu Hayuning Bawana.Keyword: Corporate Social Responsibility, Cultural Thought Java, Hamemayu Hayuning Bawana, Hermeneutics Approach